Penerapan Sistem Informasi Berbasis Aplikasi Industrial and Financial System (IFS) dalam Meningkatkan Kinerja Karyawan - Handayani, Sri Linda; Dwiridotjahjono, Jojok (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The implementation of an information system can be said to be successful if it can improve employee performance, which in turn can improve company performance. Industrial and Financial System (IFS) application at PT. XYZ helps manage existing resources, share information between departments and integrate several business operations. This article will describe the benefits of using the IFS application on employee performance. The method used is a participatory and descriptive method with literature studies and literature studies. The results of implementing the Industrial and Financial System (IFS) application information system can improve employee performance and optimize company resource management.